Response to interferons and antibacterial innate immunity in the absence of tyrosine‐phosphorylated STAT1. (12th February 2016) - Majoros, Andrea; Platanitis, Ekaterini; Szappanos, Daniel; Cheon, HyeonJoo; Vogl, Claus; Shukla, Priyank; Stark, George R; Sexl, Veronika; Schreiber, Robert; Schindler, Christian; Müller, Mathias; Decker, Thomas
Abstract: Signal transducer and activator of transcription 1 (STAT1) plays a pivotal role in the innate immune system by directing the transcriptional response to interferons (IFNs). STAT1 is activated by Janus kinase (JAK)‐mediated phosphorylation of Y701. To determine whether STAT1 contributes to cellular responses without this phosphorylation event, we generated mice with Y701 mutated to a phenylalanine (Stat1 Y701F ). We show that heterozygous mice do not exhibit a dominant‐negative phenotype. Homozygous Stat1 Y701F mice show a profound reduction in Stat1 expression, highlighting an important role for basal IFN‐dependent signaling. The rapid transcriptional response to type I IFN (IFN‐I) and type II IFN (IFNγ) was absent in Stat1 Y701F cells. Intriguingly, STAT1Y701F suppresses the delayed expression of IFN‐I‐stimulated genes (ISG) observed in Stat1 −/− cells, mediated by the STAT2/IRF9 complex. Thus, Stat1 Y701F macrophages are more susceptible to Legionella pneumophila infection than Stat1 −/− macrophages. Listeria monocytogenes grew less robustly in Stat1 Y701F macrophages and mice compared to Stat1 −/− counterparts, but STAT1Y701F is not sufficient to rescue the animals. Our studies are consistent with a potential contribution of Y701‐unphosphorylated STAT1 to innate antibacterial immunity. Synopsis: This study shows that cells and mice expressing an unphosphorylated STAT1Y701F mutant are immunodeficient, but phenotypically distinguishable from Stat1 −/− animals. STAT1Y701F expression alters innate immunity to the bacterial pathogens Listeria monocytogenes and Legionella pneumophila . High levels of cellular STAT1 protein require STAT1 tyrosine phosphorylation‐dependent tonic signaling (A). Heterozygosity of the Stat1 Y701F mutation reduces STAT1 protein expression and interferon‐induced tyrosine phosphorylation of the WT allele. STAT1Y701F inhibits nuclear translocation of STAT2 and reduces interferon‐induced transcription through STAT2/IRF9 complexes (B). Abstract : This study shows that cells and mice expressing an unphosphorylated STAT1Y701F mutant are immunodeficient, but phenotypically distinguishable from Stat1 −/− animals.